Verbal Communication in Robotics: A Study on Salient Terms, Research Fields and Trends in the Last Decades Based on a Computational Linguistic Analysis - Marin Vargas, Alessandro; Cominelli, Lorenzo; Dell’Orletta, Felice; Scilingo, Enzo Pasquale (Frontiers in Computer Science, 2021)
Verbal communication is an expanding field in robotics showing a significant increase both in the industrial and research field. The application of verbal communication in robotics is aimed to reach a natural human-like interaction with robots. In this study, we investigated how salient terms related to verbal communication in robotics have evolved over the years, what are the topics that recur in the related literature, and what are their trends. The study is based on a computational linguistic analysis conducted on a database of 7435 scientific publications of the last two decades. This comprehensive dataset was extracted from the Scopus database using specific key-words. Our results show how relevant terms of verbal communication evolved, which are the main coherent topics and how they changed over the years. We highlighted positive and negative trends for the most coherent topics and the distribution over the years for the most significant ones. In particular, verbal communication resulted to be highly relevant for social robotics. Potentially, achieving natural verbal communication with a robot can have a great impact on the scientific, societal, and economic role of robotics in the future.